Pembuatan Aplikasi Dokumentasi Jaringan - Albert Briliakta G.S; Nugroho Agus Haryono; Joko Purwadi (Jurnal Informatika, 2012)
Company networks are continually expanding to meet the needs of the company. Therefore the company must add or even change the structure of the network or network topology. In this case a network administrator must also change the network documentation ​​in accordance with the development, The documentation contains information from every device on the network. Topology changes can be difficult for network administrators in managing the network if it does not have good documentation. The application built by the author proved helpful in making the network documentation. It provide and assist network administrators in making the topology and document in the printed form that can be used as documentation of the network by the company. So it can help network administrators manage and maximize the network. Kata kunci : Network Documentation.